The Challenges of regional integration of MERCOSUR economical and commercial cooperation in the new millennium of global reality - Vega Centenos, Máximo Alfredo Ugarte (2018)
As we all know, the trend of the economy in today’s world with the scientific- technological revolution, unifies space and financial and business operations. The integration should be understood as a space whose purpose is to achieve greater economic and trade development through increased productivity, reduced costs, and training resources for the workforce and production, and educational and cultural cooperation all this through the expansion of markets, important elements of economic and social policy, as indicated by the Treaty of the Southern Common Market (MERCOSUR). It is this context, MERCOSUR has many challenges and difficulties to overcome and assess its performance; many challenges in the way of integration, in addition to concert their goals for a better development of your organization; challenges and difficulties serve as a reference and reflection for other models of Latin American integration.